Irrigation timing on barley in the cerrado region for potential yield - Guerra, Antônio Fernando (Pesquisa Agropecuaria Brasileira, 1994)
The response of barley (Hordeum vulgare L.) to six levels of soil-water tension was studied in a Clayey Dark-Red Latosol of the Brazilian savannah region. The crop was irrigated when the soil-water tension measured with tensiometers and/or gypsum blocks reached values of 37, 56, 68, 196, 570 and 1.012 kPa at a depth of 10 cm. The water was applied to the crop by using a plastic hose connected to a PVC perforated tube to assure uniform water distribution on the experimental plots. The amount of water applied in each irrigation was calculated to bring the soil profile I m depth to the field capacity (6 kPa). It was verified that barley yield was the same for the soil-water tension ranged from 37 to 570 kPa. Significant reduction in yield was verified for the higher level of soil-water tension due to reduction in the number of spikes per m2 and number of grain per spike. Among the high yield treatments, irrigation at 570 kPa resulted in lower water application for the same yield.
Keywords: soil-water tension; tensiometers; gypsum blocks